EFFECT OF LEADERSHIP AND JOB SATISFACTION ON PERFORMANCE WITH COMMITMENT MEDIATION (IN PT ALAM KAYU SAKTI SEMARANG) - Soegihartono Soegihartono (Solusi, 2019)
ABSTRACT The purpose of the research is to test and analyze whether there is aninfluence of leadership and job satisfaction on the performance of employees ofPT. Alam Kayu Sakti (PT. ALKA) Semarang by mediating organizationalcommitment. As the object of this research are permanent employees of PT. AlamKayu Sakti (PT. ALKA) Semarang with a sample of 109 employees asrespondents. The question used has been tested for validity by factor analysis andreliability with Cronbach alpha and the instruments are valid and reliable orworthy of being used as a research tool. The results of the analysis can besummarized as follows: This study can prove leadership has a positive effect on organizationalcommitment. This is in accordance with his theory Bass (1990). This study canprove job satisfaction has a positive effect on organizational commitment. This isaccording to Johlke's (2000) study. This research can prove leadership has apositive effect on performance. This is in accordance with his theory Bass (1990).This study can prove job satisfaction has a positive effect on performance. This isin accordance with his theory Robins (1996). This study proves organizationalcommitment has a positive effect on performance. This is in accordance with thestudy of Johlke et al (2000). This study does not prove that organizationalcommitment mediates on the influence of leadership on performance. This is in accordance with Tri Murdoko's research (2007). This study does not prove that organizational commitment mediates on the effect of job satisfaction onperformance. This is in accordance with Yustiani's research, Utai Dian (2005)Keywords: leadership, job satisfaction, organizational commitment and performance